2004
DOI: 10.1159/000078665
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Current Intensities above 40 μA Interfere with Current-Induced Axon-Reflex Vasodilatation in Human Skin

Abstract: When using iontophoresis, the ‘non-specific’ vasodilatation (NSV) that is observed as a result of C-fibre excitation is generally attributed to the local accumulation of protons under the anode. NSV following prolonged 100-µA anodal current application only appears after the current is stopped. Break excitation alone does not explain the delayed onset of this vasodilatation. We hypothesised that this delay could result from an anodal block and thus, that a minimal intensity would be required to achieve hyperpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, Berghoff et al, using iontophoretic administration of acetylcholine [ 18 ], showed at most a 20% reduction in the response to acetylcholine. Also, a substantial fraction of the neurogenic response can be ascribed to anodal current delivered during iontophoretic drug delivery [ 17 ]. These effects are obviated in the present study by the use of drug administration through microdialysis catheters.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Berghoff et al, using iontophoretic administration of acetylcholine [ 18 ], showed at most a 20% reduction in the response to acetylcholine. Also, a substantial fraction of the neurogenic response can be ascribed to anodal current delivered during iontophoretic drug delivery [ 17 ]. These effects are obviated in the present study by the use of drug administration through microdialysis catheters.…”
Section: Discussionmentioning
confidence: 95%
“…One might infer that it represents contributions to LDF oscillations arising from local mechanisms that may be endothelial mediated. Support for endothelial dependence of the very low‐frequency LDF oscillations originates with the work of Kvernmo using acetylcholine iontophoresis [ 14 , 15 ], although data were not definitive in untrained control subjects and were potentially confounded by the vasodilator properties of anodal current [ 16 ], which evokes a C‐fiber‐dependent axon reflex [ 17 ]. Also, acetylcholine‐dependent microvascular vasodilation in diverse tissues is axon reflex dependent [ 18 ] and may relate to other signaling molecules (e.g., prostaglandins [ 19 ] and endothelial‐dependent hyperpolarizing factor, EDHF, [ 20 ]).…”
mentioning
confidence: 99%
“…Regardless of being a frequent complaint in patients with MS, our understanding of how increases or decreases in body temperature contribute to worsening of MS symptoms is incomplete. However, as depicted in Figure 1 , the most likely mechanisms underlying heat sensitivity and the exacerbation of the symptoms of MS can be summarized as follow: Demyelinated axons in brain lesions and peripheral neurons overexpress voltage-gated Na + (Na v ) channels, particularly α-subunits, throughout their length ( Smith, 2007 ; Tartas et al, 2004 ). There have been generally revealed 9 isoforms of this type of Na v channels (Na v 1.1 to 1.9).…”
Section: Thermal Dysregulation In Ms Patients As a Challenge During Sars-cov-2 Infectionmentioning
confidence: 99%
“…The underlying mechanism of polar excitations has been mainly described from the properties of Na channels [1][2][3]. Although recent studies revisiting the mechanisms of polar excitations have proposed alternative models to the one initially described by Hodgkin and Huxley [4][5][6][7], none have suggested a contribution of ionic channels other than Na + or K + channels to the generation of polar excitation.…”
Section: Ih Channels and Polar Excitationsmentioning
confidence: 99%
“…The terminal of the stimulation triggers another action potential (equal to AE) as an off-response, because the membrane potential shifts in the depolarizing direction by breaking the stimulation. A scant few reports have revisited the mechanisms of polar excitations [4][5][6][7], but none has suggested a contribution of different ionic channels other than Na + and K + channels.…”
mentioning
confidence: 99%